Evidence of photo-induced dynamic competition of metallic and insulating phase in a layered manganite. (17th November 2015) - Li, Yuelin; Walko, Donald A; Li, Qing'an; Liu, Yaohua; Rosenkranz, Stephan; Zheng, Hong; Mitchell, J F
Abstract: We show evidence that the competition between the antiferromagetic metallic phase and the charge- and orbital-ordered insulating phase at the reentrant phase boundary of a layered manganite, La0.99 Sr2.01 Mn2 O7, can be manipulated using ultrafast optical excitation. The time-dependent evolution of the Jahn–Teller superlattice reflection, which indicates the formation of the charge and orbital order, was measured at different laser fluences. The laser-induced enhancement and reduction the Jahn–Teller reflection intensity shows a reversal of sign between earlier (~10 ns) and later (~150 ns) time delays during the relaxation after photo excitation. This effect is consistent with a scenario whereby the laser excitation modulates the local competition between the metallic and the insulating phases.